A study of predictors of occult bacteremia in febrile children 3 months to 36 months of age groups - Khurram, Mir Sumsam Ali; Reddy, U. Narayan; Khan, Khaja Amer (International Journal of Contemporary Pediatrics, 2018)
Background: The objective of the present study was to find out predictors of occult bacteremia in children, 3 months to 36 months of age group, with fever without focus and to find out most common bacteria causing occult bacteremia in the same group of children. Methods: A cross sectional study was done between January 2017 to January 2018 on hundered children between 3 months and 36 months of age group in Deccan College of Medical Sciences, Hyderabad Telangana State in all eligible children admitted in pediatric ward. A detailed history and physical examination completed as per Performa. Various blood samples were obtained for TLC, DLC including band form%, CRP, Micro –ESR and culture by standard methods. Urine sample taken in all cases for urine culture. LP and CSF analysis done in all cases. Results: Total 100 children enrolled in the study and 9 children excluded from the study. Out of 100 children included in study 25 (26%) found bacteremia positive. The study population included 60 male (60%) and 40 female (40%) children their mean and +SD age was 1997 +1.99 months. There were 20 male and 5 female and their children in bacteremia positive group compared to 40 male and 20 females in bacteremia negative group. Conclusions: The study evaluated both clinical and laboratory predictors for the detection of occult bacteremia Total 8 laboratory parameters evaluated for their significance to detect occult bacteremia.